(untitled) (Fiep Bulletin - online, 2014)
Studies demonstrate that more intense resistance exercises better the cardio respiratory condition and neuromuscular without increased hypertension risks. This study took place with the objective to investigate the cardiovascular responses and security through the Double Product (FC X PAS), during two distinct sessions of resistance hypertrophy exercise and localized muscular resistance (RML). The arterial pressure (PA) was verified using the indirect stethoscope and cardiac frequency (FC) method, using the brand Polar frequency meter, model S610i, performing two measurements for every four sets of exercise, before beginning the first repetition of the first set and soon after the last repetition of the third set. The sample was composed of six male individuals, 3 with hypertension and 3 with normal tension, with the average age being equal to 37,7 plus or minus 9,22 years of age, excluding from the sample individuals that use beta-blocker. This session of hypertrophy concluded that due to the low number of repetitions by time of exposition to the exertion, the FC rises less than 70% of the maximum FC. Although, when compared, the RML resistance training and hypertrophy by the Mann-Whitney and P-value statistic treatment, it was observed that the average gain did not differ in the training sessions. However, it is necessary to conduct new studies utilizing a larger sampling in order to validate this interpretation. The other conclusions of this study could be reviewed using a larger sample size.